Rancang Bangun Alat Ukur Kondisi Ruang Inkubator Bayi berbasis Komputer PC dan Aplikasi Android - Fivit Marwita; Ariman Ariman; Muhammad Febriansyah; Iswoko Iswoko (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2020)
The arrangement of the design of measuring instruments for room conditions in a baby incubator connected to a personal computer (PC) is intended to make it easier for care workers or technicians in health institutions to care for the baby incubator equipment, officers do not need to take measurements whose results are inputted and analyzed manually. . However, all data from the measuring instrument is connected to a computer device and an Android application. The connection between the device and the computer uses the LabVIEW (Laboratory Virtual Instrument Engineering Workbench) software, while the hardware uses the Arduino UNO. The conditions measured on this measuring instrument are at room temperature, mattress temperature, humidity and noise levels. The sensors used are temperature sensors (LM35), humidity sensors (DHT11) and sound sensors (Mic condenser). This measuring instrument will display all readings in real time on the display (LCD 20 x 4). The reading connection in the LabVIEW software will perform readings according to the settings on the baby incubator, the reading data is five times with a shift time span of five minutes. After the measurement is complete, the results will automatically enter the Microsoft Excel program, the final result of the automatic average calculation and then sent to the Android application Thus the research and tools designed can help the relevant officers to carry out routine maintenance and can control or make repairs if there is a result of poor condition (early prevention). Keyword : LabView, Arduino Uno, Android Aplication,baby Incubator